PENYELESAIAN SENGKETA PERKAWINAN BERBASIS HUKUM ADAT BALI - Nadya Herlinawati; Natasya Edisstya Ningsih; Muhammad Rifky Fauzan; Nurlailah (Jurnal Humaniora & Sosial Sains, 2025)
This study discusses the role of Balinese customary law in resolving marital disputes using the Tri Hita Karana philosophical approach. Customary law contained in Awig-Awig not only functions as a normative rule but also contains spiritual values ​​rooted in Balinese Hindu traditions. Marriage is understood as a multidimensional event that unites two large families, so that marital conflict has a significant impact on the social structure of society. The study uses a qualitative literature review method to analyze the dispute resolution mechanism and the challenges of implementing customary law in the contemporary era. The results of the study indicate that dispute resolution prioritizes deliberation and mediation based on the Tri Hita Karana principle, which emphasizes harmony between humans and God, fellow humans, and nature. This approach has proven effective in maintaining social and spiritual balance. This study confirms the relevance of customary law as an integral part of a pluralistic national legal system, as well as a fortress for preserving local wisdom amidst the flow of modernization. The research findings provide an important contribution to the development of laws that are responsive to cultural diversity.